Determinants of Obtaining COVID-19 Vaccination among Health Care Workers with Access to Free COVID-19 Vaccination: A Cross-Sectional Study - Mariam R. Elkhayat; Maiada K. Hashem; Ahmed T. Helal; Omar M. Shaaban; Ahmed K. Ibrahim; Taghreed S. Meshref; Hussein Elkhayat; Mohamed Moustafa; Mohammed Nahed Attia Mohammed; Azza M. Ezzeldin; Hebatallah G. Rashed; Alaa Bazeed; et al. (Vaccines, 2021)
Introduction: Despite global efforts to contain the illness, COVID-19 continues to have severe health, life, and economic repercussions; thus, maintaining vaccine development is mandatory. Different directions concerning COVID-19 vaccines have emerged as a result of the vaccine’s unpredictability. Aims: To study the determinants of the attitudes of healthcare workers (HCWs) to receiving or refusing to receive the vaccine. Methods: The current study adopted an interviewed questionnaire between June and August 2021. A total of 341 HCWs currently working at Assiut University hospitals offered to receive the vaccine were included. Results: Only half of the HCWs (42%) accepted the COVID-19 vaccine. The most common reason that motivated the HCWs was being more susceptible than others to infection (71.8%). On other hand, the common reasons for refusing included: previously contracted the virus (64.8%); did not have time (58.8%); warned by a doctor not to take it (53.8%). Nearly one-third of nonaccepting HCWs depended on television, the Internet, and friends who refused the vaccine for information (p < 0.05). In the final multivariate regression model, there were six significant predictors: sex, job category, chronic disease, being vaccinated for influenza, and using Assiut University hospital staff and the Ministry of Health as sources of information (p < 0.05). Conclusion: Misinformation and negative conceptions are still barriers against achieving the desired rate of vaccination, especially for vulnerable groups such as HCWs.